Economical and marketing analysis of processed hungaricum type food industrial products - Nótári, Márta; Ferencz, Árpád (Acta Agraria Kaposváriensis, 2007)
The most popular Hungaricums produced in the South Plain Region region: the apricot of Kecskemét, cherry of Kecel. An effort is made in the region to expand the range of traditional specialty products. In the world of globalisation the demand for traditional products is on the rise. This is why an effort is made in the South Plain Region to market special products specific to the region instead of the production of mass products. These unique products are competitive on the world market. We have chosed the SWOT analysis for the examination of the Hungaricums, which is supplemented with a selfevaluation. We are presenting a possible marketing strategy through the example the apricot of Kecskemét, cherry of Kecel. During our work we have studied the special processing technology of an unique Hungarian product the apricot from Kecskemét on the basis of the aspects of economy and marketing. In this essay we are talking about the activities and the effectiveness in the year of 2006 of a Hungarian enterprise dealing with processing technology of an unique Hungarian product the apricot from Kecskemét. We have highlighted a main product of the enterprise and have followed its producing technology. In the study we are aiming at the following points: The processing technology of the product; The quantity of the product sold and the acceptance price of the apricot jam; Defining the processing costs, the income and the indices of resultiveness of the product; Calculating the indices of resultativeness: Net cost, Effectiveness (economic), Profitability, Profit percentage.
Keywords: economical and marketing analysis; traditional specialty products; SWOT analisys